Análisis de la tipología de turistas del cantón Babahoyo - López Pozo, Carlos Alberto (2023)
The present investigation is focused on the "Analysis of the typology of tourists of the Babahoyo canton" having as main contribution to be able to recognize the type of tourist that visits the city. When talking about the typology of tourists, it is to focus on the identification of the demand of visitors that have the attractions that the Babahoyo canton, Province of Los Ríos, offers the tourist or visitor a unique experience in the city. Within this work, the exploratory and descriptive research methodology is applied, with a mixed approach, since to collect the information, qualitative (interviews) and quantitative (surveys) techniques are included for the collection of data on the type of tourists that arrive in the city. Babahoyo city. As a data collection technique, a questionnaire with seventeen questions was included, applied to ninety-seven respondents. On the other hand, five interviews were conducted with key actors. This gave as a final result that the tourist who visits the city of Babahoyo is for reasons of "studies or work" coming from the different cantons Montalvo, Vinces, Quevedo.